PENDAPAT SISWA SMA TENTANG GAME DRAG AND DROP SEBAGAI MEDIA INTERAKTIF PEMBELAJARAN KOSA KATA BAHASA JEPANG - Putri, Nestia Nurul Aprilliani; Setiana, Soni Mulyawan (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2023)
The purpose of this study was to find out the opinion of high school students on the Drag and Drop Game as an interactive media for learning Japanese vocabulary. The method used is the ADDIE method (Analysis, Design, Development, Implementation, Evaluation). Drag and Drop games are made using an application, namely Adobe Flash CS6. Questionnaires were used as a tool to collect student opinions and distributed to 12 extracurricular students at SMA Negeri 5 Cimahi. The results of high school students' opinions about the interactive media of Drag and Drop Game will be calculated using a Likert scale whether this Drag and Drop Game is feasible or not to be used as a learning medium. The results of the Likert scale are calculated based on the results of the number of questionnaires answered by the respondents, and the calculations obtained get a percentage of 90% results. From the percentage obtained, the Drag and Drop Game media has a very good category and deserves to be used as a medium for learning vocabulary in high school. Keywords: Vocabulary, Japanese, Interactive Media, Adobe Flash CS6